Living labs in shipping: advancing the UN Sustainable Development Goals - Anna Maria Kotrikla (Multidisciplinary Adaptive Climate Insights, 2025)
This study investigates the role of Living Labs (LLs) in creating innovative solutions for sustainable shipping, explores stakeholder involvement, issues addressed, methodologies employed, and the alignment with UN Sustainable Development Goals (SDGs). Design/Methodology/Approach: The study employs a qualitative approach, reviewing scientific and professional literature, including governmental, intergovernmental, and non-governmental documents. It identifies and analyses eight specific cases of LLs in shipping based on criteria such as industry segment, stakeholders, launching date, facilitating organization, and geographical area. The information is then tabulated to discuss stakeholders, issues addressed, and SDGs served. Findings: LLs are emerging as co-creation methods for innovative solutions in the shipping industry, primarily in the Global North. These LLs, mostly established after 2018, focus on digitalization, supply chain optimization, energy efficiency, decarbonization, and waste management. Key stakeholders align with the Triple Helix model (government, industry, academia), with a potential benefit from incorporating civil society (Quadruple Helix). The LLs contribute to multiple SDGs, notably SDG 9 (Industry, Innovation, and Infrastructure) and SDG 17 (Partnerships for the Goals). Research Implications/Limitations: A gap exists in the literature regarding the actual impact assessment of shipping LLs. The study is limited by its desk research approach, relying solely on literature. Future research should incorporate in-depth case studies with interviews for a more realistic understanding. Practical Implications/Limitations: The UN SDGs can serve as a framework for evaluating shipping innovations across environmental, social, and economic dimensions. Efficient LL processes, once validated, can be embraced by the shipping industry, contributing to its sustainability. Originality: The study provides insights into the emerging role of LLs in the shipping industry and their alignment with the UN SDGs, offering a foundation for future research and practical implementation in pursuit of a more sustainable maritime sector.   Received on, 22 March 2025 Accepted on, 17 April 2025 Published on, 04 May 2025